Pengaruh Digital Payment, e-WOM, dan Store Atmosphere Terhadap Purchase Decision pada Kaizen Heritage Cempaka Putih - Muhammad Shadiq Al Fatih; Ryna Parlyna; Fildzah Shabrina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the influence of digital payment, e-WOM, and store atmosphere on purchase decisions at Kaizen Heritage Cempaka Putih. The sample size was 120 Kaizen Heritage Cempaka Putih customer respondents. The data analysis technique used was PLS-SEM using SmartPLS version 4.1.0.9. The results showed that purchasing decisions at Kaizen Heritage Cempaka Putih were significantly and positively influenced by digital payments. This indicates that consumer purchasing decisions may be influenced by the convenience, speed, and effectiveness of digital payments. Customers are more likely to complete purchase transactions when the digital payment system is well implemented. Purchase decisions at Kaizen Heritage Cempaka Putih were positively and significantly influenced by e-WOM. This study found that before making a purchase, consumer trust is largely shaped by the experiences, recommendations, and reviews they find in digital media. Consumers may make more purchases if they receive positive information. At Kaizen Heritage Cempaka Putih, store atmosphere significantly and favorably influences customer purchasing decisions. This demonstrates that a welcoming and attractive retail environment, supported by well-designed layout, lighting, and customer service, can create a satisfying shopping experience and attract customers to purchase.